2010
DOI: 10.1007/s10800-010-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxodisulfate generation on boron-doped diamond microelectrodes array and detection by scanning electrochemical microscopy

Abstract: In this work, the electrogeneration of peroxodisulfate from a 1 M H 2 SO 4 solution on boron-doped diamond microelectrodes array has been studied. The peroxodisulfate is detected at the vicinity of the boron doped diamond electrode, with the SECM probe, only when the polarization of the microarray is greater than 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…Previously, a higher mineralisation of a model compound was achieved during anodic oxidation on BDD in the chloride-free medium (Murugananthan et al, 2008;Scialdone et al, 2009). In electrooxidation at BDD in the presence of SO 2À 4 , long-lived persulfate ions (S 2 O 2À 8 ) are generated via direct electron transfer and/or via reaction with the generated OH by forming sulfate radicals (SO $À 4 ) as intermediates (Khamis et al, 2010;Ozcan et al, 2008). Sulfate radical is an excellent one-electron oxidant, with a standard redox potential (E 0 ) of 2.6 V vs. SHE (Liang et al, 2007).…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a higher mineralisation of a model compound was achieved during anodic oxidation on BDD in the chloride-free medium (Murugananthan et al, 2008;Scialdone et al, 2009). In electrooxidation at BDD in the presence of SO 2À 4 , long-lived persulfate ions (S 2 O 2À 8 ) are generated via direct electron transfer and/or via reaction with the generated OH by forming sulfate radicals (SO $À 4 ) as intermediates (Khamis et al, 2010;Ozcan et al, 2008). Sulfate radical is an excellent one-electron oxidant, with a standard redox potential (E 0 ) of 2.6 V vs. SHE (Liang et al, 2007).…”
Section: 4mentioning
confidence: 99%
“…The measured total HAAs and total THMs concentrations were 13.6 and 1.9 mM in Na 2 SO 4 , and 1.1 and 0.2 mM, in NaNO 3, respectively. This could be explained by the oxidation of Cl À to reactive chloro-species in the bulk by S 2 O 2À 8 ions, and/or in the vicinity of the electrode surface by SO $À 4 radicals (Khamis et al, 2010;Provent et al, 2004). Therefore, bulk electrochlorination and formation of THMs and HAAs is enhanced in the presence of sulfate through indirect oxidation.…”
Section: 5mentioning
confidence: 99%
“…nitrate, 4-nitrophenol [49][50][51], Cr(VI) ions, Ag(I) ions, sulphate, peroxodisulfate [43], hydrogen peroxide [55]), for bio-detections (e.g. detection of dopamine [44][45][46][47][48], neuronal activity measurements [52,53], quantal catecholamine secretion from chromaffine cells [54]), and for the generation and detection of peroxidisulfate with the aid of scanning electrochemical microscope (SECM) [59]. We have shown that dopamine can be sensitively and selectively detected on diamond ultramicroelectrode arrays in the presence of ascorbic acid [55].…”
Section: Diamond Micro-and Ultramicro-electrode Arraysmentioning
confidence: 99%
“…Several hundreds of reviews [26], [27] and [28] were published on applications of these electrodes in cyclic voltammetry for the analysis of pesticides, herbicides, pharmaceutical products [29], [30] and [31]. The conductive diamond was also used to manufacture electrodes for electrochemical detection in HPLC and flow injection [32], [33], [34], [35], [36], [37] and [38] electrochemical reactions [39].…”
Section: Introductionmentioning
confidence: 99%
“…The applications were extended to arrays of microelectrodes [39], [40] and [41]. The techniques employed for manufacturing the diamond arrays of electrodes where more or less sophisticated, from photolithography up to pattern the isolation surface with a powerful laser beam [42].…”
Section: Introductionmentioning
confidence: 99%